The performance optimization video collection. (O'Reilly, 2016)
"Even as computers have grown faster, the Web has grown heavier. Seemingly trivial differences in load time and responsiveness can make a huge difference in user response. These talks help you prioritize performance, integrate it with your development process, and make users happy."--Resource description page.